2018
DOI: 10.1177/1010539518813604
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Spatial and Contextual Factors Influencing Intraregional Differences in Child Vaccination Coverage in Bangladesh

Abstract: In Bangladesh, policy discourse has mostly focused on regional inequities in health, including child immunization coverage. Knowledge of local geographical and contextual factors within regions, however, becomes pertinent in efforts to address these inequities. We used the Bangladesh Demographic and Health Survey 2011 to examine factors that influence intraregional differences in vaccination coverage using a multilevel analysis. We found that in spite of the provision of health facilities at each level of admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Across SSA, the effect of spatial access on immunisation uptake has been varied. Some studies found travel time to health facilities to be an important determinant of child immunisation [ 15 , 18 , 19 , 30 , 64 ] while others did not find a significant association [ 29 , 65 , 66 ]. These varied findings were attributed to intra-regional disparities between urban and rural regions depicting an ‘urban advantage’ due to high density of health centers that reduced the effect of travel time on child immunisation outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across SSA, the effect of spatial access on immunisation uptake has been varied. Some studies found travel time to health facilities to be an important determinant of child immunisation [ 15 , 18 , 19 , 30 , 64 ] while others did not find a significant association [ 29 , 65 , 66 ]. These varied findings were attributed to intra-regional disparities between urban and rural regions depicting an ‘urban advantage’ due to high density of health centers that reduced the effect of travel time on child immunisation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple contacts with health facilities are required to achieve full immunisation status [ 17 ]. However, long distances and increased travel times (spatial accessibility) remains a major barrier to expanding immunisation coverage in many SSA countries [ 15 , 18 , 19 ]. This is more pronounced in the rural areas, where most of the unvaccinated children live and where services are limited [ 20 , 21 ] and in informal settlement that are densely populated and often affected by significant traffic delays [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6] In comparison, countries and regions in the Northern Hemisphere have higher coverage rates. On a more micro-scale, regional differences have been shown in studies examining the distribution of vaccination coverage among regions in Asia, such as Bangladesh, [7] Mongolia, [8] and Indonesia. [9] Studies examining geographic differences in immunisation coverage include those that determined association of immunisation coverage with either individual-level characteristics (maternal age and education), [10,11] or regional-level factors (urban versus suburban areas, [12,13] access to good health care providers, [14] and the state of social infrastructure in areas of residence).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial access to a health facility, especially in sub-Saharan Africa (SSA) countries, is a signi cant determinant of DTP3 vaccination coverage as the vaccine is mainly administered during routine immunisation schedules at health facilities [11][12][13]. Studies have shown that rural areas [14,15] and densely populated informal settlements [16,17] are most affected by poor access to healthcare services.…”
Section: Introductionmentioning
confidence: 99%